Viability of fecal DNA extracted from spotted deer’s fecal samples preserved in technical grade ethanol for non-invasive DNA analysis - Muhammad Zulfiqar Meizar Pratama; Tuty Arisuryanti (Department of Biology, Faculty of Sci and Tech, Universitas Islam Negeri Alauddin Makassar, 2022)
.